Divergent genes in potential inoculant Sinorhizobium strains are related to DNA replication, recombination, and repair. (16th February 2016) - Penttinen, Petri; Greco, Dario; Muntyan, Victoria; Terefework, Zewdu; De Lajudie, Philippe; Roumiantseva, Marina; Becker, Anke; Auvinen, Petri; Lindström, Kristina
Abstract : To serve as inoculants of legumes, nitrogen‐fixing rhizobium strains should be competitive and tolerant of diverse environments. We hybridized the genomes of symbiotically efficient and salt tolerant Sinorhizobium inoculant strains onto the Sinorhizobium meliloti Rm1021 microarray. The number of variable genes, that is, divergent or putatively multiplied genes, ranged from 503 to 1556 for S. meliloti AK23, S. meliloti STM 1064 and S. arboris HAMBI 1552. The numbers of divergent genes affiliated with the symbiosis plasmid pSymA and related to DNA replication, recombination and repair were significantly higher than expected. The variation was mainly in the accessory genome, implying that it was important in shaping the adaptability of the strains.